PENGARUH MOTIVASI EKSTRINSIK, KOMPENSASI FINANSIAL DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN OKUI CREATIVE HUB CABANG KEDIRI - Hardiningrum, Iing Sri (AMMER : JOURNAL OF ACADEMIC & MULTIDICIPLINE RESEARCH; Vol 1 No 01 (2021): September 2021, 2021)
This study has a limitation on the aspect of human resource management to determine the effect of extrinsic motivation, financial compensation and organizational culture on employee performance at Okui Creative Hub, Kediri Branch. By using a saturated sample of 30 respondents and using research methods of observation, interviews, documentation, questionnaires or questionnaires and decision studies. As well as the data analysis technique of this study using statistical tests through validity and reliability tests, classical assumption tests, multiple linear regression tests, hypothesis testing, coefficient tests of determination using SPSS for windows version 26.0. Based on the analysis, it is found that extrinsic motivation (X1), financial compensation (X2), and organizational culture (X3) variables have a significant effect simultaneously or jointly on employee performance (Y) with a significant value of (0.008 < 0.05). Partially, the extrinsic motivation variable has no significant effect on employee performance with a significant value of (0.830 > 0.05), the financial compensation variable partially has a significant influence on employee performance with a value of (0.016 < 0.05), the organizational culture variable is partially partial has a significant effect on employee performance with a value of (0.011 <0.05)